Concordism in «Royal Commentaries» - Eguiguren Callirgos, Luis (Mercurio Peruano, 2016)
It has pointed out by several authors the presence of a concordist philosophy as a background in the Royal Commentaries. It proposed in this study to pay attention to the possibility that such concordism may fundamentally ingrained in the Christianity of the author, according to the teachings of the Catholic Church. The peculiar humanistic formation of Inca Garcilaso would stand in harmonious cooperation with these teaching; founded on the philosophy of love and applied to the social and political aspects.